The 1580 Political Ordinance of the States of Holland and West Friesland: Certain Examples of its Influence in the English-Speaking World - Haitas, Daniel (Pro Futuro, 2021)
A tanulmány az Egyesült Holland Tartományokra és Nyugat-Frízföldre vonatkozóan 1580-ban kiadott “politikai rendeletnek” az angolszász világra gyakorolt hatását vizsgálja, különös tekintettel a Massachusettsi Nemzetközösségben ma élő Plymouth-kolóniára és Dél-Afrikára. Az előbbit illetően az elemzés arra koncentrál, hogy a Plymouth-kolóniába érkező zarándokok (pilgrimek) miképpen vezették be a polgári házasság intézményét a közösségben, továbbá az említett intézmény fejlődésének holland gyökereit is feltárja. Ezek után a házastársak közötti, végrendelet nélküli öröklési rendet ismerteti, és történeti szempontból elemzi annak változásait az 1580-as, az öröklési rendszert e területen módosító jogszabály alapján.The present study deals with certain influences the 1580 Political Ordinance of the States of Holland and West Friesland had in the English-speaking world, specifically in relation to the Plymouth Colony in the present-day Commonwealth of Massachusetts and South Africa. Regarding the former, there is a survey of the introduction of the institution of civil marriage by the Pilgrims at the Plymouth Colony and the Dutch background to this particular development. In relation to South Africa, there is an analysis of the lack of intestacy inheritance between spouses in that country in the past due to the system of inheritance rooted in the 1580 Political Ordinance, and the changes that took place in connection to this with the passing of time.